Pengaruh Personal Branding Komedian terhadap Minat Pembelian Tiket Pertunjukan Komedi - Arifriyanto Wibowo; Farid Rusdi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The growth of the digital entertainment industry has prompted public figures to build strong personal branding to influence audience consumption decisions, including in the context of purchasing tickets for comedy shows. This study examines the extent to which Indonesian comedian Raditya Dika’s personal branding, developed through Instagram, can increase interest in purchasing tickets for comedy shows advertised via the @ekresaofficial account. This study aims to evaluate the impact of personal branding based on self-image theory. This study employs a quantitative methodology using a survey technique. The findings indicate that Raditya Dika’s personal branding exerts a beneficial and significant influence on audiences’ propensity to purchase comedy show tickets. These results reinforce the notion that a stronger personal brand positively correlates with audiences’ propensity to make purchasing decisions. Thus, personal branding is proven to be a crucial element in shaping consumer behavior within the digital entertainment sector. Pertumbuhan industri hiburan digital mendorong tokoh publik untuk membangun personal branding yang kuat guna memengaruhi keputusan konsumsi audiens, termasuk dalam konteks pembelian tiket pertunjukan komedi. Penelitian ini mengkaji sejauh mana personal branding komedian Indonesia, Raditya Dika, yang dikembangkan melalui media Instagram, dapat meningkatkan minat untuk membeli tiket pertunjukan komedi yang diiklankan melalui akun @ekresaofficial. Penelitian ini bertujuan untuk mengevaluasi dampak personal branding yang berlandaskan teori citra diri. Studi ini menggunakan metodologi kuantitatif, dengan menggunakan teknik survei. Temuan menunjukkan bahwa personal branding Raditya Dika memberikan pengaruh yang bermanfaat dan signifikan terhadap kecenderungan penonton untuk membeli tiket pertunjukan komedi. Hasil ini memperkuat anggapan bahwa citra pribadi yang lebih baik berkorelasi positif dengan kecenderungan penonton untuk mengambil keputusan pembelian. Dengan demikian, personal branding terbukti sebagai elemen penting dalam membentuk perilaku konsumen di sektor hiburan digital.